Current characterization methods for cellulose nanomaterials - Foster, E Johan; Moon, Robert J; Agarwal, Umesh P; Bortner, Michael J; Bras, Julien; Camarero-Espinosa, Sandra; Chan, Kathleen J; Clift, Martin J D; Cranston, Emily D; Eichhorn, Stephen J; Fox, Douglas M; Hamad, Wadood Y; et al. (Chemical Society reviews, 2018)
A new family of materials comprised of cellulose, cellulose nanomaterials (CNMs), having properties and functionalities distinct from molecular cellulose and wood pulp, is being developed for applications that were once thought impossible for cellulosic materials. Commercialization, paralleled by research in this field, is fueled by the unique combination of characteristics, such as high on-axis stiffness, sustainability, scalability, and mechanical reinforcement of a wide variety of materials, leading to their utility across a broad spectrum of high-performance material applications. However, with this exponential growth in interest/activity, the development of measurement protocols necessary for consistent, reliable and accurate materials characterization has been outpaced. These protocols, developed in the broader research community, are critical for the advancement in understanding, process optimization, and utilization of CNMs in materials development. This review establishes detailed best practices, methods and techniques for characterizing CNM particle morphology, surface chemistry, surface charge, purity, crystallinity, rheological properties, mechanical properties, and toxicity for two distinct forms of CNMs: cellulose nanocrystals and cellulose nanofibrils.